Labelling Fish Diets with 15n -Leucine for Monitoring Feed Consumption and Bio-Distribution in Atlantic Salmon - Aspee-Lamas, A (John Wiley and Sons Inc, 2022)
Feeding represents 50–70% of the cost of production in salmon farming, higher than any other animal farm. The improvement of this percentage is challenging as the food is thrown into the fish tank, there is no quantification of the amount of food that is consumed by the fish. In consequence, it is difficult to adjust the food composition making it more nutritive or promoting food consumption by fish. In this study, to investigate food consumption, bio-distribution and food residues, leucine containing 15N (a stable isotope of nitrogen) was used to label the fish food. Atlantic salmon (Salmo salar) weighing 100–120 g were maintained in 30 L tanks at a density of 14 kg/m3. Fishes were fed daily at 1% of the fish weight with pellet labelled with 15N-leucine. The 15N incorporation was determined 14 hours after the feeding in all the fish organs. Results showed that 14 hours after the administration of a single dose of labelled food to Atlantic salmon enables the detection of the tracer in the whole organism allowing determining the food consumption. Through the analysis of nitrogen use efficiency (NUE), we showed that the trunk, pyloric caeca and head incorporate the highest level of the marker (72.7, 8.7 and 5.7%, respectively). This methodology would permit monitoring feeding to minimize food loss, improve administration methodologies or select the preferred foods for the fish, among others to reduce production costs. © 2022 The Authors. Veterinary Medicine and Science published by John Wiley & Sons Ltd.